Eprosartan effects on intravascular platelet activity in patients with arterial hypertension and metabolic syndrome - I. N. Medvedev; T. A. Kumova (Российский кардиологический журнал, 2008)
Aim: To study therapeutic effects of eprosartan on intravascular platelet activity in patients with arterial hypertension (AH) and metabolic syndrome (MS). Material and methods: In total, 32 participants received eprosartan (600 mg/d) for 4 months. Dynamics of lipid peroxidation in plasma and platelets, antioxidant potential of blood serum and platelets, intravascular platelet activity were assessed. The data were analyzed using Student’s t test. Results: In individuals with AH and MS, eprosartan therapy reduced lipid peroxidation and optimized intravascular platelet activity. Long?term eprosartan treatment could strengthen this beneficial effect. Conclusion. To decrease body weight in persons with AH and MS, eprosartan should be combined with non?pharmaceutical methods.